Persepsi Generasi Z atas Mitologi Golan & Mirah dalam Perspektif Sosiologi Komunikasi - Prasetyo, Ady; Murdianto, Murdianto; Wathoni, Syamsul (Social Science Academic, 2024)
Golan and Mirah mythology is a form of oral culture originating from the city of Ponorogo, East Java. This story is a myth believed by the people of Ponorogo. This research aims to explore how Gen Z views the Golan and Mirah mythology and how their perceptions are influenced by social media and digital technology. This research will also analyze the role of communication in spreading and maintaining the relevance of this mythology amidst changing times. This research uses a qualitative descriptive method. Data collection techniques using interview and documentation techniques. This research uses social identity theory, which is an accumulation of group values that are adapted into an individual's self-concept. The results of this research show that Gen Z has a complex relationship with the Golan and Mirah mythology, which is influenced by the context of social media, cultural consumption and globalization. Despite the challenges of preserving traditional values, Gen Z continues to find meaning and relevance in these mythologies through adaptation and reinterpretation. To contribute to existing research, this article also attempts to map the landscape of Gen-Z Society's Perception of Golan & Mirah Mythology: A Communication Sociology Perspective.